Confirmation of Monod Model for Biofiltration of Styrene Vapors from Waste Flue Gas - Reza Dehghanzadeh; Babak Roshani; Mahzar Asadi; Mohammad Fahiminia; Ahmad AslHashemi (Tabriz University of Medical Sciences, 2012)
Background: The objective of this research was to investigate the kinetic behavior of the biofil-tration process for the removal of styrene.Methods: A three stage compost based biofilter was inoculated with thickened activated sludge. The reaction order rate constants were obtained from continuous experiments and used as the specific growth rate for the Monod equation.Results: The measured concentration profiles show a linear dependence on the bed height in the biofilter at higher loadings, such as 75 and 45 g m-3 h-1. This is the condition of reaction limitation for a reaction with zero-order kinetics. From the experimental data, maximum elimination capac-ity (ECmax) was estimated to be 44, 40 and 26 g m-3 h-1 at empty bed retention times (EBRTs) of 120, 60 and 30 s, respectively. However, at lower loadings, the measured concentration profile of the biofilter is one of exponential increase, which is the condition of both reaction and diffusion limitations for a reaction with zero-order kinetics. Maximum elimination capacities found from the experimental results were the same as Monod model predictions. Both the experimental re-sults and the model predictions showed the influence of EBRT on the removal rate of styrene, particularly for the highest loading rate.Conclusion: In terms of the practical applications of the proposed models have the advantage of being simpler than Monod kinetics and Monod kinetics requires a numerical solution.